2013
DOI: 10.2105/ajph.2013.301314
|View full text |Cite
|
Sign up to set email alerts
|

Launching Native Health Leaders: Reducing Mistrust of Research Through Student Peer Mentorship

Abstract: Introduction Mistrust of higher education institutions influences the college experiences of many American Indian and Alaska Native (AI/AN) students. Launching Native Health Leaders (LNHL) was a peer-mentoring and networking program that introduced AI/AN undergraduates to health and research careers and concepts of community-based participatory research (CBPR). The LNHL engaged students in group dialogue about research practices in AI/AN communities while providing career development through professional confe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 18 publications
(24 reference statements)
0
7
0
Order By: Relevance
“…Aboriginal community leaders gave a variety of responses about their understanding and experiences with research, and some reported the word did not exist in their language. Similarly, James et al reports that when Native American participants were asked about research they were frustrated because they believed the concept of research was embedded solely in Western values [ 40 ]. Some Aboriginal community leaders in the Fitzroy Valley denied any research experience, but went on to describe various science, art and land-rights projects with which they were involved.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aboriginal community leaders gave a variety of responses about their understanding and experiences with research, and some reported the word did not exist in their language. Similarly, James et al reports that when Native American participants were asked about research they were frustrated because they believed the concept of research was embedded solely in Western values [ 40 ]. Some Aboriginal community leaders in the Fitzroy Valley denied any research experience, but went on to describe various science, art and land-rights projects with which they were involved.…”
Section: Discussionmentioning
confidence: 99%
“…Research projects that worked well in the community had common features e.g. researchers took time to understand the culture and engage the community before conducting research; the most well respected studies employed local people, providing employment and research capacity building [ 3 , 4 , 14 – 19 , 23 , 27 , 28 , 40 – 46 ]. Participants mentioned they were pleased with the way they were engaged for The Picture Talk Project and said that it was being done ‘the right way’.…”
Section: Discussionmentioning
confidence: 99%
“…This underinvolvement of adolescents in health research may be attributed to the challenges or barriers experienced by researchers and adolescents contributing to research projects 17. These challenges include a lack of awareness of the evidence on youth involvement,19 81 a need for extensive training to effectively engage youth in research,17 19 48 57 81–87 limited training resources and a lack of a comprehensive set of guidelines on engaging youth in health research,19 48 81 88 89 inadequate funding to support meaningful youth involvement,83 86 90 difficulties in recruiting and retaining adolescents,86 87 91 complex ethical procedures such as additional consent and assent requirements, and compliance with different safeguarding practices that vary for different contexts 49 57 92. To address some of the highlighted challenges to meaningful youth involvement, we aim to develop a comprehensive set of guidelines for involving youth in health research.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, AI/ANs are the most underrepresented minority in STEM fields and in higher education overall. Training AI/AN researchers to conduct well-designed community health research is essential to foster community trust in research, increase community participation in research, and create sustainable improvements in AI/AN health and life expectancy (Becker et al, 2005;James et al, 2013;Warne, 2006). Minority researchers in principal investigator roles have the trust of their community and tend to focus on those diseases or risk factors that disproportionately affect their communities (Ginther et al, 2011;Shavers et al, 2005).Historically mistrustful of research and outside researchers, tribes are recognizing the value of community health research as a "tool of tribal sovereignty" (National Congress of American Indians, n.d.…”
mentioning
confidence: 99%